The Relationship between Parenting Stress Level and the Tendency Toward Violent Behavior in Children - Hilaliyah, Nurul; Anggeriyane, Esme; Noorhasanah, Evy (Indonesian Journal of Global Health Research, 2024)
Parental stress is often associated with the occurrence of child abuse, as stress may lead parents to engage in violent behaviors under the guise of discipline. Such violence can significantly affect children's developmental outcomes in a lasting manner. This research aimed to ascertain the relationship between the level of parenting stress and violent behavior in children. This quantitative study used a cross-sectional design. Data was collected by 79 mothers with first-grade students at Muhammadiyah 9 Elementary School in Banjarmasin using total sampling. The bivariate analysis with Spearman’s rank correlation showed a significant relationship between parenting stress level and violent behavior in children (p-value= 0.000, α <0.05), with a correlation coefficient of 0.698. The results showed that there was a strong positive correlation. It means that lower levels of parenting stress are associated with reduced violent behavior in children. Effective stress management and a good parenting approach are recommended to minimize the risk of violence for children.